Entrepreneurial drops: The role of narrative in the simple organic brand - Coltro, Amabile; Oliveira, Giulia Loreto Lovo de (Seven Editora, 2024)
The aim of this article is to explore the relationship between brand narrative and entrepreneurship, as evidenced in this case study of the Brazilian brand Simple Organic. A thorough literature review reveals that brand narrative is a communication strategy and a tool that can shape the very essence of an enterprise. It can be concluded that, throughout the journey of this natural and organic cosmetics brand, narratives play a crucial role in building the brand’s identity, influencing consumer perceptions, and contributing to entrepreneurial success. The choice of Simple Organic as the subject of study is justified by its remarkable rise in the market and its authentic approach, communicating identity, values, and commitments through various channels, from social media to product packaging. This study highlights the importance of this strategic communication in brand perception. Ultimately, this research expands our academic understanding and provides practical guidance for entrepreneurs and marketing professionals seeking to build authentic and impactful brands. DOI:https://doi.org/10.56238/sevened2023.006-129